2017
DOI: 10.1111/jop.12564
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α (−308G>A) and TNF‐R1 (36A>G) single nucleotide polymorphisms are strong risk factors for odontogenic keratocystic tumor development

Abstract: Our findings suggest that the two polymorphisms are strong risk factors for KCOT development in Serbian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, Salles et al (2017) have reported the association between TNF‐α (−308 G >A) polymorphism and acute AP. The present results are also in line with previously conducted studies in Serbian populations regarding functional polymorphisms in TNF‐α gene and the risk of peri‐implantitis (Rakic et al 2015) and odontogenic keratocystic tumour (Ilic et al 2017) development, both suggesting that homozygous carriers of the variant A allele are significantly more prone to disease development.…”
Section: Discussionsupporting
confidence: 92%
“…However, Salles et al (2017) have reported the association between TNF‐α (−308 G >A) polymorphism and acute AP. The present results are also in line with previously conducted studies in Serbian populations regarding functional polymorphisms in TNF‐α gene and the risk of peri‐implantitis (Rakic et al 2015) and odontogenic keratocystic tumour (Ilic et al 2017) development, both suggesting that homozygous carriers of the variant A allele are significantly more prone to disease development.…”
Section: Discussionsupporting
confidence: 92%
“…Maybe, the frequency difference between study populations with higher prevalence in Asian and American population may be explained by genetic susceptibility and polymorphism of some gene groups, as happens in odontogenic keratocystic tumour 67 and ameloblastoma; 68 however, no study evaluated this characteristic for OM.…”
Section: Discussionmentioning
confidence: 99%
“…Another common subject of the investigation was genes related to proinflammatory cytokines and tissue degradation enzymes. Genes encoding interleukins IL‐1α, IL‐1β, and tumor necrosis factor TNF‐α and its receptor TNF‐R1 were analyzed in three studies (Eshghyar et al., 2012; Ilic et al., 2017; Sengüven & Oygür, 2011), and one study evaluated polymorphisms of matrix metalloproteinases MMP9 and MMP2 genes (Aloka et al., 2019).…”
Section: Resultsmentioning
confidence: 99%